Genes and their single nucleotide polymorphism involved in innate immune response in central nervous system in bacterial meningitis: review of literature data - Gowin, Ewelina (Inflamm Res, 2018)
BACKGROUND: There are many studies analysing the effect of SNPs in genes coding proteins which are involved in innate immune response on susceptibility to invasive bacterial disease. Many of them gave inconclusive results. Regarding the complexity of immune response and cooperation between particular elements, number of SNPs may have a cumulative effect on the susceptibility to bacterial meningitis. FINDINGS: In most studies cooccurrence of several SNPs was not analysed. These studies were performed on small groups of patients and usually only few SNPs were checked simultaneously. Additionally, comparison of the results across the studies is hard to conduct. We hypothesise that the number of variants of genes involved in innate immune response plays a role in susceptibility to bacterial meningitis. However, the role of toll-like receptors and other part of innate immune response in the eradication of bacteria, and initiation of the inflammatory response in CNS need further studies. CONCLUSION: Large multicentre studies assessing multiple SNPs in patients with microbiologically proven pneumococcal or meningococcal meningitis are needed to find real genetic risk factors for developing bacterial meningitis. This is necessary to design more effective treatment and prevention strategies for severe infections.